The Effect of Firm Size, Audit Committee, Auditor Reputation, and Leverage on Audit Quality of Manufacturing Companies Listed on the Indonesia Stock Exchange (BEI) for 2019-2023 Period - Intan S, Agnes Dui; Siahaan, Grace Marlina; Br Nadeak, Sisilia Mona Bresipa; Ayang Pratama; Lubis, Yeti Meliany (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
This study investigates the impact of firm size, audit committee, auditor reputation, and leverage on audit quality among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Utilizing a purposive sampling method, the study selected 60 companies based on specific criteria; consistently listed on the IDX, availability of comprehensive data for all independent variables, and no delisting throughout the observation period. This resulted in a total of 300 firm-year observations analyzed by multiple linear regression. The empirical results demonstrate that firm size, audit committee, auditor reputation, and leverage simultaneously exert a significant influence on audit quality. Furthermore, partial analysis reveals that while firm size, audit committee, and auditor reputation significantly affected audit quality, leverage did not have a statistically significant impact.